Microsatellite instability—a useful diagnostic tool to select patients at high risk for hereditary non-polyposis colorectal cancer: a study in different groups of patients with colorectal cancer. Issue 6 (1st June 1999) - Lamberti, C; Kruse, R; Ruelfs, C; Caspari, R; Wang, Y; Jungck, M; Mathiak, M; Malayeri, H R H; Friedl, W; Sauerbruch, T; Propping, P
Abstract : BACKGROUND: Clinical diagnosis of hereditary non-polyposis colorectal cancer (HNPCC) is based on a typical family history. As molecular genetic testing is predominantly restricted to these families, gene carriers not meeting the clinical criteria may be missed. AIMS: To examine the value of microsatellite instability (MSI) as a tool to increase the likelihood for uncovering a mismatch repair germline mutation in patients with colorectal cancer and to identify a genotype-phenotype relation in families with verified mutations. METHODS: Systematic search for germline mutations (hMSH2 and hMLH1 genes) was performed in 96 patients: 57 fulfilled the Amsterdam criteria (group 1) and 12 the looser HNPCC criteria (group 2). Seventeen patients showed familial clustering of cancers (group 3) and 10 patients under 50 years had sporadic cancer (group 4), the latter of whom all exhibited MSI + tumours. RESULTS: A similar proportion of germline mutations was found in patients who fulfilled the clinical criteria of HNPCC and had MSI + tumours (groups 1 and 2; 15/39) compared with patients who did not meet these clinical criteria but who had MSI + tumours (groups 3 and 4; 8/27 patients). Affected relatives of patients with hMLH1 mutations showed a significantly higher frequency of colorectal cancer but a lower frequency of endometrium cancer than those with hMSH2 mutations. CONCLUSIONS: MSI in tumour tissue is a useful criterion for selecting patients who should be tested for germline mutations in the mismatch repair genes hMSH2 and hMLH1 irrespective of their family history. Among carriers of hMSH2 mutations the tumour spectrum was broader than among carriers of hMLH1 mutations.